(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
A quantitative analysis of the in-plane shear test results reported in PhD thesis of Hafeth Bu Jldain was preformed in this paper. Analysis of the results was conducted from experimental and analytical bases. It was conducted experimentally through comparing the results obtained for uO-APT samples with the results obtained for samples made from an industrial fabric manufactured by GmbH Saertex. The analytical validation was conducted through systematic Taguchi plans. These plans investigate, the effect of the type of reinforcement (A and B), the effect of the number of layers, and the effect of stitching setup (R-45, R+45, R0 and R90) on the behavior of the reinforcements. The plans primarily analyzed the extent to which the reinforcement may shear and the force required to do so. Shear test results for stitching orientation R-45 and R+45 show the ability of the new fabric to shear under lower shear forces, which ranged between 0 N and 25 N needed to shear uO-APT reinforcements to shear angles ranging from 50° to 55° before wrinkling was observed.